Measuring vitamin D levels: surrogates are insufficient. Issue 1 (31st October 2014) - Heald, A. H.; Anderson, S. G.; Scargill, J. J.; Short, A. D.; Holland, D.; Livingston, M.; Fryer, A. A.; Donn, R. P.
Summary Aims With the increasing evidence of adverse consequences because of low vitamin D levels on health demand for vitamin D, screening is increasing. The objective of the study was to assess whether parathyroid hormone (PTH) levels/bone profile is sufficient to identify patients with vitamin D insufficiency or deficiency, or whether vitamin D should be measured directly. Methodology A total of 1560 serum specimens, with requests for 25‐hydroxyvitamin D (25‐OH vitamin D), calcium, phosphate, alkaline phosphatase (ALP), creatinine and PTH on the same sample were analysed at Salford Royal Hospital from November 2010 to November 2012. Results The prevalence of total vitamin D insufficiency or deficiency (defined as total 25‐OH vitamin D < 50 nmol/l) was 62.9% (981/1560) overall, with males having higher proportions (67.2 vs. 59.3 per cent; χ2 = 8.78, p = 0.003). There was no overall trend in mean serum adjusted calcium across categories of 25‐OH vitamin D status but mean serum phosphate was significantly lower (F = 6.53, p < 0.0001) in patients with a 25‐OH vitamin D level < 50 nmol/l. However in patients with vitamin D deficiency, a significant proportion had PTH, calcium, phosphate and alkaline phosphatase levels within the laboratory normal range. Even at a 25‐OH vitamin D < 10 nmol/l, 71.6% had a normal PTH, 89.8% had normal serum calcium levels, 84.9% had normal phosphate levels and 81.6% had normal serum ALP. Conclusions Therefore, despite the costs associated with the measurement of vitamin D, our findings show that no surrogate is adequate for screening for vitamin D deficiency.